Online monitoring system on controlled irrigation experiment for export quality mango in Thailand - Eriko Yasunaga (2018)
© Springer International Publishing Switzerland 2016. Export quality fresh mango fruit requires a careful management from production to distribution in order to meet a high standard specifically for a long supply chain. In this paper, we describe our online monitoring system to observe responses of mango trees to different levels of irrigation intensities, based on which an optimal irrigation regime can be established. The system consists of different sensors for soil moisture content, sap-flow, photographs, and so on. To fully control the amount of water irrigated, rain-out shelter was installed for every tree for the experiment. Field observation data are used to compute water consumption and water stress of target trees. Preliminary results supported the practicality of this system that can further be used for quantitative assessment and numerical simulation for optimizing a production system aiming at a long supply chain.